Watkins Family Gathering at Home of Frances Kamp - Watkins, Howard::::::::: (1988)
Seated: Christine Watkins, Robin Watkins, and Adam Watkins; Sanding: Frances Kamp, Rose O'Reilley, Albert Watkins, Batsheva Eitan (Howard's Aunt from Israel), and Howard Watkins